Toward a theory of peace: the role of moral beliefs - Forsberg, Randall (Cornell University Press, 2019)
The idea of a theory of peace -- Conditions for the abolition of war -- The roles of innate impulses and learned moral beliefs in individual and group violence -- Socially sanctioned group violence : features, examples, and sources -- Ritual cannibalism : a case study of socially sanctioned group violence -- Sanctioned violence, morality, and cultural evolution -- Appendix : the debate on the existence of cannibalism.